2010
DOI: 10.1111/j.1600-0463.2010.02650.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of self‐renewing immature dendritic cells from mouse spleen that can take up mycobacteria and present antigens to T cells

Abstract: Dendritic cells (DC) play a key role in driving the adaptive immune response to Mycobacterium tuberculosis (MTB), the causative pathogen of tuberculosis (TB). However, studying these important yet very sparse immune cells in the context of MTB pathogenesis is severely restricted by the lack of suitable cell lines and the complexity of culturing of DC progenitors, usually obtained from the bone marrow. However, significant advances have been made towards generating long-term DC cultures from various lymphoid ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Unexpectedly, our results also showed an intracellular distribution of M. tuberculosis in CD3 ϩ T lymphocytes. Previous studies have shown that dendritic cells, a derivative from the lymphocyte precursor, can phagocytize M. tuberculosis and exert their antigenpresenting functions (11,23). These findings together prompt us to propose that lymphocytes play a similar role in TBM, compensating for the decreased antigen-presenting function of macrophages.…”
Section: Discussionmentioning
confidence: 74%
“…Unexpectedly, our results also showed an intracellular distribution of M. tuberculosis in CD3 ϩ T lymphocytes. Previous studies have shown that dendritic cells, a derivative from the lymphocyte precursor, can phagocytize M. tuberculosis and exert their antigenpresenting functions (11,23). These findings together prompt us to propose that lymphocytes play a similar role in TBM, compensating for the decreased antigen-presenting function of macrophages.…”
Section: Discussionmentioning
confidence: 74%
“…3A). For testing the ability of ICM to bind to APC, we generated mouse spleen derived APC as described previously [25]. Their phenotype was analysed by surface molecule staining and they were found to be positive for CD16/32 (93%), CD11b (98%), CD11c (65%) and MHC II (51%) (not shown), consistent with myeloid dendritic cells and macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…1×10 6 spleen-derived APC, prepared as described by Pal et al [25], were re-suspended in 100 µL of PBS containing 5% BSA. ICMs (10 µg/mL) were added and cells incubated on ice for 2 h. Unbound protein was removed by repeated (3x) addition of the binding buffer and recovery of cells by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, immature dendritic cells established from the mouse spleen grow in suspension and can take up mycobacteria (21). We therefore thought that cells of a lymphocyte cell line could be a good host for reconstituting apoptotic cell engulfment, when coupled with the pHrodo-labeled apoptotic cell engulfment assay.…”
Section: Discussionmentioning
confidence: 99%